2002
DOI: 10.1063/1.1479470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructures and crystalline defects on the superconductivity of MgB2

Abstract: This work studies the influence of microstructures and crystalline defects on the superconductivity of MgB 2 , with the objective to improve its flux pinning. A MgB 2 sample pellet that was hot isostatic pressed (HIPed) was found to have significantly increased critical current density (J c ) at high fields than its un-HIPed counterpart. The HIPed sample had a J c of 10000 A/cm 2 in 50000 Oe (5 T) at 5K. This was 20 times higher than that of the un-HIPed sample, and the same as the best J c reported by other r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 21 publications
7
60
0
Order By: Relevance
“…Other structural defects, such as vacancies, interstitials, substitutions, or stacking faults, 11 are other possible reasons for the observed lattice strain. It has been reported that there is a correlation between the resistivity and the lattice strain, 12 as can be seen in the inset of Fig. 3͑a͒.…”
Section: Resultsmentioning
confidence: 79%
“…Other structural defects, such as vacancies, interstitials, substitutions, or stacking faults, 11 are other possible reasons for the observed lattice strain. It has been reported that there is a correlation between the resistivity and the lattice strain, 12 as can be seen in the inset of Fig. 3͑a͒.…”
Section: Resultsmentioning
confidence: 79%
“…The microstructure of all doped samples exhibits small grains, while the undoped sample presents larger grains ͑ϳ1 m͒. 18 . Figure 4 illustrates the microstructure of ͑a͒ SiC and ͑b͒ swCNT samples with regions of grains from 20 to 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier attempts succeeded in raising the intragrain J c through the incorporation of Mg͑B 1−x O x ͒ 2 , 1 SiC, 2,12,13 Al, 3 Dy 2 O 3 , 4 nano-C, 5 and carbon nanotubes, 6,12,[14][15][16] which produce a decrease in the critical temperature ͑T c ͒ by chemical substitution and probably lattice strain. 17 The improvement of intergrain J c in bulk samples is related to grain connectivity 18 and may be achieved by optimizing the processing parameters ͑i.e., ultrasonication, 16 HIPing, 18 applying magnetic field during the sintering process, 19 etc.͒. The best results for H c2 ͑0͒ and J c at high field ͑H Ͼ 5 T͒ and 4 K in polycrystalline samples were achieved using C and SiC, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although considerable progress has already been made, it is still true that the best critical current densities J c reported so far on MgB 2 wires or tapes fabricated using the powder-in-tube (PIT) method are well below those of bulk samples prepared under high pressure. 2,3,4 To optimize J c in MgB 2 wires and tapes, we need a deeper understanding on how fabrication and processing conditions affect microstructure and vortex pinning. Some general facts have been established.…”
Section: Submitted To Aplmentioning
confidence: 99%